Association of Obesity and Socioeconomic Status among Women of Childbearing Age Living in Urban Area of Morocco. (29th July 2018) - Barich, Fatima; Zahrou, Fatima Ezzahra; Laamiri, Fatima Zahra; El Mir, Nisrine; Rjimati, Manelle; Barkat, Amina; Rjimati, El Arbi; Aguenaou, Hassan
Abstract : Worldwide, obesity is considered as an important public health problem. This study aims to explore the social and economic factors associated with overweight and obesity among women of childbearing age residing in the urban area of Morocco. This is a descriptive and analytical study conducted among women (N = 240 ), aged between 15 and 49 years. At recruitment, socioeconomic status (SES) of each participant was assessed, anthropometric parameters were recorded, and body mass index (BMI), waist circumference, and waist-to-hip ratio (WHR) were measured to assess overweight and obesity. Data regarding skipped meals (breakfast, lunch, and dinner) were collected using an adapted questionnaire. The prevalence of overweight and obesity among women of childbearing age was 29.9% and 15.4%, respectively, while for abdominal obesity, the prevalence of overweight and obesity was, respectively, 39.9% and 60.1%. The results indicate that the prevalence of overweight and obesity among women is higher in women aged over 30. A significant association was shown between education level and both BMI and WHR (r 1 = − 0.23, r 2 = − 0.17, p < 0.05 ), respectively, and there is also a significant correlation between household size and WHR abdominal obesity (r = 0.21, p = 0.05 ). Our results reinforce the necessity to improve the access of all social classes in Morocco to reliable information on the determinants and consequences of obesity and to develop plans for adequate prevention and management of obesity.